Pressure-induced Lifshitz transition in NbP: Raman, x-ray diffraction, electrical transport, and density functional theory - Gupta, Satyendra Nath; Singh, Anjali; Pal, Koushik; Muthu, D. V. S.; Shekhar, Chandra; Qi, Yanpeng; Naumov, Pavel G.; Medvedev, Sergey A.; Felser, Claudia; Waghmare, U. V.; Sood, A. K. (Physical Review B, 2018)
We report high-pressure Raman, synchrotron x-ray diffraction, and electrical transport studies on Weyl semimetals NbP and TaP along with first-principles density functional theoretical (DFT) analysis. The frequencies of first-order Raman modes of NbP harden with increasing pressure and exhibit a slope change at Pc∼9 GPa. The pressure-dependent resistivity exhibits a minimum at Pc. The temperature coefficient of resistivity below Pc is positive as expected for semimetals but changes significantly in the high-pressure phase. Using DFT calculations, we show that these anomalies are associated with a pressure-induced Lifshitz transition, which involves the appearance of electron and hole pockets in its electronic structure. In contrast, the results of Raman and synchrotron x-ray diffraction experiments on TaP and DFT calculations show that TaP is quite robust under pressure and does not undergo any phase transition.
CRIS-Team Scopus Importer:2022-04-14